Controversies on Tumor Thickness Versus Nodal Metastasis in Oral Squamous Cell Carcinomas Revealed: A Histopathologist’s Perspective - Reddy, Vandana; Wadhwan, Vijay; Reddy, Munish; Venkatesh, Arvind (Indian Journal of Medical and Paediatric Oncology, 2018)
Background: Cervical metastasis has a tremendous impact on prognosis in patients with head and neck squamous cell carcinomas (HNSCCs). However, to date management of clinically negative neck in HNSCC is still a controversial subject. Tumor thickness (TT) is a strong predictor for lymph node involvement in oral squamous cell carcinomas (SCCs). However, controversy exists about the optimal TT cutoff point for a clinically relevant risk to the neck. Aim and Objectives: The aim is to evaluate the relationship between TT and the risk of cervical lymph node involvement and to determine optimal TT cutoff point for prompting prophylactic neck management. Materials and Methods: The clinical files and histological sections of 35 SCC (T1/T2) at buccal mucosa site from clinically determined N0 patients were retrospectively analyzed who underwent surgical treatment of their primary lesion with simultaneous neck dissection. An ocular micrometer was used to measure the TT both in exophytic and ulcerated lesions. Chi-square contingency tables were used to correlate TT and other clinicopathological parameters with metastasis in the neck. Results: Clinically, negative necks turned out pathologically positive in 42.8% (n = 15/35). In the group in which tumor depth exceeded 1.5 mm, the metastatic rate was 86.7% (13/15). In contrast, when the depth of invasion was <1.5 mm, the incidence of cervical metastasis was 13.3% (2/15) irrespective of the 2 stages. Conclusion: TT is a highly significant, objectively measurable prognostic factor in early stage oral cancers and elective neck therapy is indicated for tumors exceeding 1.5 mm invasion.
Keywords: Elective neck therapy; metastasis; oral squamous cell carcinoma